Characterization and isolation method of Gigantochloa scortechinii (Buluh Semantan) cellulose nanocrystals - Nor Izaida, Ibrahim; Mohamed Thariq, Hameed Sultan; Andrzej, Łukaszewicz; Ain Umaira Md, Shah; Farah Syazwani, Shahar; Jerzy, J´ozwik; Muhammad Imran, Najeeb; Rafał, Grzejda (Elsevier, 2024)
This study explored the impact of sodium hydroxide (NaOH) and the benzoylation treatment on the production of cellulose nanocrystals (CNCs) derived from Semantan bamboo (Gigantochloa scortechinii). Bamboo cellulose nanocrystals (BCNs) were obtained via acid hydrolysis, with the effectiveness of an isolation method and chemical treatments demonstrated in removing non-cellulosic constituents. X-ray diffraction analysis revealed a crystalline cellulose II structure for benzoylated BCN (B) and a crystalline cellulose I structure for NaOH-treated BCN (S), with BCN (S) exhibiting a higher crystallinity index (80.55%) compared to BCN (B) (67.87%). The yield of BCN (B) (23.68 ± 1.10%) was higher than that of BCN (S) (20.65 ± 2.21%). Transmission Electron Microscopy (TEM) images showed a mean diameter of 7.95 ± 2.79 nm for BCN (S) and 9.22 ± 3.38 nm for BCN (B). Thermogravimetric analysis (TGA) indicated lower thermal stability for BCN (B) compared to BCN (S), with char residue contents at 600°C of 31.06% and 22 %, respectively. Zeta potential values were -41.60 ± 1.97 mV for BCN (S) and -21.80 ± 2.54 mV for BCN (B). Gigantochloa scortechinii bamboo holds significant potential for sustainable and eco-friendly applications in the construction, furniture, and renewable energy industries. These findings highlight the versatility and potential of BCNs derived from G. scortechinii for various applications.